2021
DOI: 10.1038/s41598-021-81701-x
|View full text |Cite
|
Sign up to set email alerts
|

PGMD/curcumin nanoparticles for the treatment of breast cancer

Abstract: The present study aims at developing PGMD (poly-glycerol-malic acid-dodecanedioic acid)/curcumin nanoparticles based formulation for anticancer activity against breast cancer cells. The nanoparticles were prepared using both the variants of PGMD polymer (PGMD 7:3 and PGMD 6:4) with curcumin (i.e. CUR NP 7:3 and CUR NP 6:4). The size of CUR NP 7:3 and CUR NP 6:4 were found to be ~ 110 and 218 nm with a polydispersity index of 0.174 and 0.36, respectively. Further, the zeta potential of the particles was − 18.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 84 publications
2
23
0
Order By: Relevance
“…On increasing the treatment duration, the rate of migration of MDA-MB231 cells was reduced greatly as compared with the controls (cells alone, PLGA-blank NPs and naked curcumin) as shown in Figure 5. Interestingly, from the images which were captured during the migration studies, it was observed that free curcumin did not contribute significantly towards affecting the migration of the cells (Figures 6 & 7) as stated by Kumari et al [18]. Free curcumin, instead, killed the cells rather than affecting the migration of cells.…”
Section: Discussionmentioning
confidence: 50%
“…On increasing the treatment duration, the rate of migration of MDA-MB231 cells was reduced greatly as compared with the controls (cells alone, PLGA-blank NPs and naked curcumin) as shown in Figure 5. Interestingly, from the images which were captured during the migration studies, it was observed that free curcumin did not contribute significantly towards affecting the migration of the cells (Figures 6 & 7) as stated by Kumari et al [18]. Free curcumin, instead, killed the cells rather than affecting the migration of cells.…”
Section: Discussionmentioning
confidence: 50%
“…CUR has been shown to suppress cell growth in different cancer cells in the past. [ 32,33 ] However, compared to CUR, mPEG‐CUR and mPEG‐CUR@Au caused higher cytotoxicity. As demonstrated in Figure 3c, drug combinations with X‐ray irradiation eliminated more cancer cells than CUR, and mPEG‐CUR at each concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The IR spectra of raw materials and drug-loaded fibers were obtained to explore the possible compatibility of components ( Figure 3 b). The characteristic peaks at 3510, 1602, 1506, and 1152 cm −1 of Cur demonstrate hydroxyl (-OH), carbonyl (-C=O), olefins (-C=C-), and ether (-C-O) groups, respectively [ 45 , 57 , 58 ]. The characteristic -C=O groups of PHBV and PVP were observed in 1720 and 1649 cm −1 , respectively [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%